Bupropion and the risk of sudden death: a self-controlled case-series analysis using The Health Improvement Network. Issue 10 (29th July 2005) - Hubbard, R; Lewis, S; West, J; Smith, C; Godfrey, C; Smeeth, L; Farrington, P; Britton, J
Abstract : Background: Bupropion is an effective smoking cessation therapy but its use in the UK has been limited by concerns that it may increase the risk of sudden death. Methods: Data for all patients prescribed bupropion within The Health Improvement Network (a computerised general practice database) were extracted and the self-controlled case-series method was used to estimate the relative incidence of death during the first 28 days of treatment. The incidence of seizures, a recognised adverse effect of bupropion, was also investigated during this period. Results: A total of 9329 individuals had been prescribed bupropion (mean age 44 years, 48% male). The total person-time after the first prescription for bupropion was 17 586 years, and during this time 121 people died. Two people died within the first 28 days of treatment, which was less than expected in comparison with the remaining observation period by an incidence ratio of 0.50 (95% confidence interval (CI) 0.12 to 2.05). Twenty eight people were recorded as having a total of 45 seizures (23 before starting bupropion, two in the first 28 days of treatment, and 20 at a later point). The relative incidence of seizures during the first 28 days of treatment was 3.62 (95% CI 0.87 to 15.09), equivalent to one additional seizure per 6219 first time bupropion users. Conclusions: Bupropion use is probably associated with an increased risk of seizures, but no evidence was found to suggest that the drug is associated with an increased risk of sudden death.